Socio Demographic Profile And Awareness Among Sanitation Workers In Aligarh (Indian Journal of Public Health Research & Development, 2024)
The workers maintaining cleanliness in cities are popularly known as sanitation workersthroughout India. Sanitation Worker refers to all sorts of workers engaged in cleaning jobs, who handle dry and wet waste, and those who sweep. They are exposed to a variety of chemicals which pose an occupational hazard by exposing them to a wide range of health problems. Therefore this study has been undertaken, to assess the sociodemographic profile and awareness among sanitation workers in Aligarh. Across-sectional study was conducted in Aligarh including Sanitation workers under Nagar Nigam.The study period was one year, i.e.from July 2018 to June 2019. A total of  450 Sanitation workers were studied in a cross sectional study using multistage sampling conducted on sanitation workers employed under Nagar Nigam, Aligarh using structured questionnaires. The Questionnaire used in the study included Socio-demographic characteristics, Standard of Living Index, Health Problems,Health Seeking Behaviour and Satisfaction from Health System,Quality of Life, Stigma and Discrimination, Occupational Health Hazards, Alcohol Consumption and General Awareness. Data was entered and analyzed in SPSS 20. Data entry and analysis were presented using descriptive statistics, which included percentages, means, and frequencies. In this study, males constituted most of the respondents, reflecting male dominance in urban municipal work. Urban residents accounted for 95.8%, likely due to employment-driven migration. Marital status was varied, with 80.9% married. As almost all of the Safai Karamchari were unaware of government schemes.The older age group of 41-50 years was found having higher health problems. On the analysis of health problems with the mean age of Sanitation workers, it was found to be significantly associated with a higher age. There is a need to acknowledge, improve and strengthen services, including improving the working environment and better health care to the sanitation workers.
Keywords: sanitation workers,awareness,health problems.